KEMAMPUAN MENGIDENTIFIKASI MAJAS SISWA - Juwita Sari Pebriani; Kahfie Nazaruddin; Edi Suyanto (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem discussed in this research is how is the ability of students of grade VIII in SMP Negeri 21 Bandar Lampung on identifying figure of speech (metaphor, personification and hyperbole) in poems. The research aims to describe the level of students’ ability to identify the figure of speech (metaphor, personification and hyperbole). In this reasearch used descriptive method. The population of this research were 308 students’ distributed in 8 classes 80 (25%) of them were randomly chosen to be taken as the research sampel. The data were collected by using the technique of writing test. The results of the research shows that the ability of VIII grade students of SMPN 21 Bandar Lampung to identify the figure of speech (metaphor, personification and hyperbole) in poems is poor with 57,87% on average.Kata kunci : identifikasi majas, kemampuan, puisi